Discursive construction of corporate identity through websites: An intercultural perspective on the commercial banks of the United States and China - Fu, Heng; Zhu, Huifen (Frontiers in Psychology, 2022)
With the assistance of the corpus analysis tool Wmatrix 4.0, this paper analyzes the semantic categories of the top 10 commercial banks of China and the US to figure out their social cultural behavior in the internet business context. It is discovered that both common and distinctive identities were constructed: the common identities include the professional financial service provider, responsible corporation for employees and relevant communities with environmental and social consciousness;While the distinctive identities are manifested in the communication strategy, style and persuasion mode: (1) The Chinese Commercial Banks adopted the proactive strategy for corporate identity construction, are prone to take hierarchical and impersonal communication style, and more focused on the “credibility appeal” and “rational appeal” in persuasion mode; (2) the commercial banks of the US are more reactive in the communication strategy, position themselves in short distance with the putative audience in communication style, and conform to the typical “affective appeal” regarding the persuasion mode. From the intercultural perspective, the distinctions are the representation of the peculiar high-context culture and low-context culture based on Hofstede’s Cultural Dimensions Theory. Chinese banks should try to shorten the cultural gap by adopting communication strategy in conformity with the local cultural when going global rather than sticking to the domestic communication strategy.